The analysis of extraction and memory analysis forensic tool for searching cryptographic key in volatile memory [electronic resource] - Nordiana Rahim, 1987- (2012)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2012